Bβ(15–42) Attenuates the Effect of Ischemia-Reperfusion Injury in Renal Transplantation - Sörensen, Inga (American Society of Nephrology, 2011)
Renal ischemia-reperfusion contributes to reduced renal allograft survival. The peptide Bβ(15–42), a breakdown product of fibrin, attenuates inflammation induced by ischemia-reperfusion in the heart by competitively blocking the binding of leukocytes to endothelial VE-cadherin, but whether it could improve outcomes in renal transplantation is unknown. Here, we tested the ability of Bβ(15–42) to ameliorate the effects of renal ischemic injury during allogenic kidney transplantation in mice. In our renal transplantation model (C57BL/6 into BALB/c mice), treatment with Bβ(15–42) at the time of allograft reperfusion resulted in significantly improved survival of recipients during the 28-day follow-up (60% versus 10%). Bβ(15–42) treatment decreased leukocyte infiltration, expression of endothelial adhesion molecules, and proinflammatory cytokines. Treatment significantly attenuated allogenic T cell activation and reduced cellular rejection. Moreover, Bβ(15–42) significantly reduced tubular epithelial damage and apoptosis, which we reproduced in vitro. These data suggest that Bβ(15–42) may have therapeutic potential in transplant surgery by protecting grafts from ischemia-reperfusion injury.